2013
DOI: 10.1186/1746-6148-9-235
|View full text |Cite
|
Sign up to set email alerts
|

Anaplasma phagocytophilum strains from voles and shrews exhibit specific ankA gene sequences

Abstract: BackgroundAnaplasma phagocytophilum is a Gram-negative bacterium that replicates obligate intracellularly in neutrophils. It is transmitted by Ixodes spp. ticks and causes acute febrile disease in humans, dogs, horses, cats, and livestock. Because A. phagocytophilum is not transmitted transovarially in Ixodes spp., it is thought to depend on reservoir hosts to complete its life cycle. In Europe, A. phagocytophilum was detected in roe deer, red deer, wild boars, and small mammals. In contrast to roe deer, red d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 50 publications
(83 reference statements)
5
45
0
Order By: Relevance
“…Co‐occurrence of these tick species has previously been suggested as a mechanism whereby pathogens such as A. phagocytophilum and B. microti could be maintained in wild rodent populations by I. trianguliceps and transferred to I. ricinus feeding on the same hosts, which could then act as a bridge vector to transmit the infectious agents to humans (Bown et al , ). However, further research has since shown that distinct ecotypes of A. phagocytophilum are found in discrete enzootic cycles involving specific host species, and that the ecotype detected in small rodents and I. trianguliceps is not present in I. ricinus (even those feeding on infected rodents) or in other types of host (Bown et al , Majazki et al , Blaňarová et al , Jahfari et al ). Therefore it might be argued, based upon this evidence, that A. phagocytophilum circulating in small mammals is unlikely to present a disease risk for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Co‐occurrence of these tick species has previously been suggested as a mechanism whereby pathogens such as A. phagocytophilum and B. microti could be maintained in wild rodent populations by I. trianguliceps and transferred to I. ricinus feeding on the same hosts, which could then act as a bridge vector to transmit the infectious agents to humans (Bown et al , ). However, further research has since shown that distinct ecotypes of A. phagocytophilum are found in discrete enzootic cycles involving specific host species, and that the ecotype detected in small rodents and I. trianguliceps is not present in I. ricinus (even those feeding on infected rodents) or in other types of host (Bown et al , Majazki et al , Blaňarová et al , Jahfari et al ). Therefore it might be argued, based upon this evidence, that A. phagocytophilum circulating in small mammals is unlikely to present a disease risk for humans.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we and other authors have hypothesized that roe deer could be reservoir hosts for their own A. phagocytophilum variants [1]. Additionally, other data indicate that red deer could be reservoir hosts for domestic ruminant variants, but not for human, dog, or horse variants [69]. Wild boars ( Sus scrofa ) are also suspected to be reservoir hosts for human A. phagocytophilum variants [8, 10].…”
Section: Introductionmentioning
confidence: 99%
“…based on serology) [70] and Iran (34.3% based on PCR) [71]. While it has been demonstrated that several animal species may act as reservoirs of A. phagocytophilum [72,73], the role of camelids remains to be ascertained. In the same way, the competence of Hyalomma spp.…”
Section: Discussionmentioning
confidence: 99%